Perlindungan Hukum Terhadap Pelanggan Jasa Telekomunikasi Dalam Registrasi Kartu Seluler Prabayar Melalui Gerai - Alfons, Gilberth; Saija, Ronald; Pariela, Marselo Valentino Geovani (PATTIMURA Law Study Review, 2024)
Technological advancements in Indonesia have made life easier for the public, particularly in telecommunications with the advent of smartphones. However, this technology also brings the risk of cybercrime. To protect personal data, the government mandates the registration of prepaid cards with National Identification Numbers (NIK) and Family Card numbers (KK). Nevertheless, the legal protection of personal data in this process remains a subject of debate. This research aims to understand the form of legal protection for personal data of telecommunications service users in light of the mandatory registration of prepaid cards and the legal implications of this registration requirement. This research employs a normative legal study of descriptive-analytical nature and uses a statutory approach. What There are two forms of legal protection for personal data under the prepaid card registration law: preventive and repressive. Preventive protection is provided by Article 17 of the Minister of Communication and Informatics Regulation No. 12 of 2016 (amended by Regulation No. 21 of 2017) and Article 15 of Regulation No. 20 of 2016 on Data Protection. Repressive protection is under Article 95A of Law No. 24 of 2013 on Population Administration and Article 51(1) of Law No. 19 of 2016 on ITE. Legal implications include mandatory registration, centralized validation, penalties for data leaks, and restrictions on data disclosure.